Environmental History Modulates Arabidopsis Pattern-Triggered Immunity in a HISTONE ACETYLTRANSFERASE1–Dependent Manner . Issue 6 (24th June 2014) - Singh, Prashant; Yekondi, Shweta; Chen, Po-Wen; Tsai, Chia-Hong; Yu, Chun-Wei; Wu, Keqiang; Zimmerli, Laurent
Abstract : This work shows that repetitive exposure to mild stresses increases Arabidopsis resistance to bacteria by priming the pattern-triggered immunity response in a HISTONE ACETYLTRANSFERASE1–dependent manner, demonstrating a mechanistic link between the primed state and epigenetics. Abstract: In nature, plants are exposed to a fluctuating environment, and individuals exposed to contrasting environmental factors develop different environmental histories. Whether different environmental histories alter plant responses to a current stress remains elusive. Here, we show that environmental history modulates the plant response to microbial pathogens. Arabidopsis thaliana plants exposed to repetitive heat, cold, or salt stress were more resistant to virulent bacteria than Arabidopsis grown in a more stable environment. By contrast, long-term exposure to heat, cold, or exposure to high concentrations of NaCl did not provide enhanced protection against bacteria. Enhanced resistance occurred with priming of Arabidopsis pattern-triggered immunity (PTI )–responsive genes and the potentiation of PTI -mediated callose deposition. In repetitively stress-challenged Arabidopsis, PTI -responsive genes showed enrichment for epigenetic marks associated with transcriptional activation. Upon bacterial infection, enrichment of RNA polymerase II at primed PTI marker genes was observed in environmentally challenged Arabidopsis . Finally, repetitively stress-challenged histone acetyltransferase1-1 ( hac1-1 ) mutants failed to demonstrate enhanced resistance to bacteria, priming of PTI, and increased open chromatin states. These findings reveal that environmental history shapes the plant response to bacteria through the development of a HAC1-dependent epigenetic mark characteristic of a primed PTI response, demonstrating a mechanistic link between the primed state in plants and epigenetics.